POTENSI LIMBAH DAN KARAKTERISTIK PROSES PENGOMPOSAN TANDAN KOSONG KELAPA SAWIT YANG DITAMBAHKAN SLUDGE LIMBAH PABRIK MINYAK KELAPA SAWIT - Firman L Syahwan (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2010)
Empty Fruit Bunches (EFB) and sludge are 2 (two) kinds of solid waste of palm oilplant that haven’t been utilized optimally. Their potency are high enough, and both have different characteristic that positively influence each other if both utilized together. The research result showing that composting process of EFB added by sludge is optimally aerobic done with processing time about 13 weeks to produce mature compost. The addition of sludge is positively influence composting process of EFB that its compost product has good quality.Key words : crude palm oil, empty fruit bunches, sludge, composting.